Physical Activity Relate to Cardiovascular Resilience in Grade X and XI Students of SMA 01 Muhammadiyah Medan in 2022 - Pakpahan, Komar; Yunafri, Andri (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Physical activity is a form of any physical movement that requires the expenditure of energy produced by skeletal muscles, such as work, play or recreational activities. Cardiovascular resilience is the ability of the lungs, heart and blood vessels to deliver oxygen and nutrients to cells to meet the needs of activity. The purpose of this study is to determine the relationship between physical activity and cardiovascular resilience in students of grades X and XI of SMA 01 Muhammadiyah Medan. The research method used is an analytical method with a cross sectional approach. The number of samples used was 118 students. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ) and cardiovascular endurance was measured using the Harvard Step Test. This study had 118 respondents with students who did physical activity, the majority of whom were 81 (68.6%) students. For cardiovascular endurance, the majority is lacking, around 82 (69.5%) students. Meanwhile, for the chi-square test, a p-value of 0.023 was obtained , so that there was a significant relationship between physical activity and cardiovascular endurance in SMA 01 Muhammadiyah Medan students. There is a significant relationship between physical activity and cardiovascular resilience in students of SMA 01 Muhammadiyah Medan.